HCMV-Encoded NK Modulators: Lessons From in vitro and in vivo Genetic Variation - Patel, Mihil; Vlahava, Virginia-Maria; Forbes, Simone K.; Fielding, Ceri A.; Stanton, Richard J.; Wang, Eddie C. Y. (Frontiers in Immunology, 2018)
Human cytomegalovirus (HCMV) is under constant selective pressure from the immune system in vivo. Study of HCMV genes that have been lost in the absence of, or genetically altered by, such selection can focus research towards findings of in vivo significance. We have been particularly interested in the most pronounced change in the highly passaged laboratory strains AD169 and Towne – the deletion of 13-15kb of sequence (designated the UL/b’ region) that encodes up to 22 canonical genes, UL133-UL150. At least 5 genes have been identified in UL/b’ that inhibit NK cell function. UL135 suppresses formation of the immunological synapse (IS) by remodelling the actin cytoskeleton, thereby illustrating target cell cooperation in IS formation. UL141 inhibits expression of two activating ligands (CD155, CD112) for the activating receptor CD226 (DNAM-1), and two receptors (TRAIL-R1, R2) for the apoptosis-inducing TRAIL. UL142, ectopically expressed in isolation, and UL148A, target specific MICA allotypes that are ligands for NKG2D. UL148 impairs expression of CD58 (LFA-3), the co-stimulatory cell adhesion molecule for CD2 found on T and NK cells. Outside UL/b’, studies on natural variants have shown UL18 mutants change affinity for their inhibitory ligand LIR-1, while mutations in UL40’s HLA-E binding peptide differentially drive NKG2C+ NK expansions. Research into HCMV genomic stability and its effect on NK function has provided important insights into virus:host interactions, but future studies will require consideration of genetic variability and the effect of genes expressed in the context of infection to fully understand their in vivo impact.